2017
DOI: 10.1007/s40820-017-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of N-Doped Graphene-Like Carbon Nanoflakes as Efficient and Stable Electrocatalysts for the Oxygen Reduction Reaction

Abstract: A series of N-doped carbon materials (NCs) were synthesized by using biomass citric acid and dicyandiamide as renewable raw materials via a facile one-step pyrolysis method. The characterization of microstructural features shows that the NCs samples are composed of few-layered graphene-like nanoflakes with controlled in situ N doping, which is attributed to the confined pyrolysis of citric acid within the interlayers of the dicyandiamide-derived g-C3N4 with high nitrogen contents. Evidently, the pore volumes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…The RDE measurements confirmed that FePc shows a high intrinsic ORR activity (Fig. S10), superior to commercial Pt/C in 0.1 M KOH [65,66]. Figure 6b displays the charge polarization curves of the two air electrodes (FePc + Ni 3 FeN and Pt/C + RuO 2 ) in ZAB, implying a better charge performance of Ni 3 FeN than RuO 2 as confirmed by its higher current densities at the same potential.…”
Section: Rechargeable Zn-air Batterymentioning
confidence: 62%
“…The RDE measurements confirmed that FePc shows a high intrinsic ORR activity (Fig. S10), superior to commercial Pt/C in 0.1 M KOH [65,66]. Figure 6b displays the charge polarization curves of the two air electrodes (FePc + Ni 3 FeN and Pt/C + RuO 2 ) in ZAB, implying a better charge performance of Ni 3 FeN than RuO 2 as confirmed by its higher current densities at the same potential.…”
Section: Rechargeable Zn-air Batterymentioning
confidence: 62%
“…9 Subsequently, N-doped graphene and graphitic flakes were extensively synthesized and most reported samples can efficiently electrocatalyze the ORR via a four-electron pathway in alkaline fuel cells, which possessed better catalytic activity, stability, and tolerance to methanol crossover effect than Pt/C. [11][12][13][14][15] Following this pioneering work, various heteroatom-doped carbon materials were investigated, such as B-doped CNTs or graphene (BG), 16,17 sulfur-doped graphene (SG), [18][19][20][21] phosphorous-doped graphite layers, 22 iodine-doped graphene 23 , and edge-halogenated (Cl, Br or I) graphene nanoplatelets (GnPs). 24 For example, Antonietti's group developed mesoporous N-doped carbon materials with high surface area of 1500 m 2 g −1 by carbonization of nucleobases dissolved in an all-organic ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…51,52 These peaks are attributed to the C]O group (the 1st), the carbonyl oxygen atom in the ester, the amide in the hydroxyl or ether, the anhydride and the carbonyl oxygen atom (the 2nd), the ether oxygen atom in the ester and anhydride (the 3rd) and the atoms in the oxygen carboxyl group (the 4th). 46,47 Similarly, the co-existence of pyridine nitrogen (398.3 eV), pyrrole/pyridone-N (400.2 eV) and pyridine-N-oxygen (402.7 eV) Table 1 Specific surface areas and pore volumes of CTSPC-2 and CTSHPC-x in CTSHPC-2 is demonstrated in the N1s spectrum (Fig. 7d).…”
Section: Morphology and Microstructural Characterizationmentioning
confidence: 82%
“…The reason for this is that KOH activation may result in the loss of doped nitrogen content, which is similar to the reported literature. [45][46][47][48][49] In order to further determine the surface chemical composition of CTSHPC-2 carbon material, the C1s, O1s, and N1s spectra of the samples were carefully analyzed by the peak tting method, as shown in Fig. 7b-d.…”
Section: Morphology and Microstructural Characterizationmentioning
confidence: 99%